Congenital melanocytic nevus. - Bonifazi, E.; Mazzotta, F.; Garofalo, L. (European Journal of Pediatric Dermatology, 2001)
Definition. Congenital melanocytic nevus is a mole consisting of epidermal melanocytes and nevus cells, present at birth. The melanocyte derives from the neural crest, reaches the epidermis during the fetal life and here persists throughout life, particularly in the basal layer. By routine staining, melanocytes are characterized by a light, perinuclear halo. By special staining, its cytoplasmatic prolongations or dendrites get visible. Through its dendrites, melanocytes transfer to the surrounding cells -keratinocytes- their product, namely melanin. The melanocytic nevus probably arises form a post-mutational clonal proliferation (9). Initially, techae of melanocytes are present at the dermal-epidermal junction, then going down into the dermis and loosing the contact with the epidermis. The lack of contact with the epidermis is probably responsible for morphological and functional changes such as disappearance of dendrites and stopped production of melanin, leading to the transformation of the melanocyte in nevus cell. (...)